Honduras as a Complex Adaptive System and What It Means for the European Union – The Case of Violence - Kai Enno Lehmann (German Institute of Global and Area Studies (GIGA), 2016)
This paper assesses why the various initiatives undertaken by the European Union in Honduras have not had the desired impact of reducing the extraordinary levels of violence in the country. The hypothesis put forward is that the EU's approach to the issue of violence has been unsuccessful because it does not match the complexity of the problem encountered. As an alternative, the paper puts forward complexity and human systems dynamics as conceptual frameworks for reinterpreting the issue of violence. It shows that violence is one of the results of an incoherent process of self-organisation which marks Honduras and suggests ways of influencing the conditions that make up this pattern in order to address the problem of violence. It also outlines what this new approach would mean for the actions and policies proposed and implemented by the European Union.
Keywords: 300; European Union; Honduras; violence; complexity; human systems dynamics